Establishing an immanent counterhumanism for the un-foreclosure of the future: Deleuze, Mbembe, Hartman and the anarchic Open World - Berti, Daniel Jonathan (Department of Philosophy, 2022)
This dissertation addresses the political form of the human, its multiply-stratified nature, and the world it makes up - by focusing first on a tension between two broad kinds of approaches in philosophy of race that intend to unmake that stratification. One, called counterhumanism and exemplified by the work of Sylvia Wynter, is deeply prevalent in antiracist struggles, and argues that a false image of the human is at the core of oppression, that a new, all-inclusive image must be fostered to replace it. The other, nonhumanism, emerges from some Deleuzo-Guattarian scholarship as a contingent critique of transcendence – value frameworks imposed from outside – and argues that no model is adequate to the complexity of reality - that State thought, the kind of thinking involved in such modelling, is inherently conservative rather than liberatory, maintaining a more fundamental oppressive element. The second part of the dissertation teases out some core developments in Achille Mbembe's conceptual and historical cartography of race and the human in Critique of Black Reason (2017), ones that avoid the issue of transcendence in counterhumanism. On his account, contemporary race begins with the European creation of an enclosure that claims humanness for itself, excluding those from the World-outside. Through negative resentment critique and positive critiques based in calculated creation (e.g. religious and artistic), Mbembe resolves the tension in creating an immanent counterhuman as dis-enclosed world, through immanent and transversal thinking. The political form of the human as understood here is fundamentally tied to all aspects of human relations, and as such when changed will come with a corresponding fundamental change in our political arrangements. This final part of the dissertation expands Mbembe's human as the Open world, to outline the various social and political arrangements compossible with it. This part answers how we may organise ourselves politically to seek humanness in the present, less-than-human, enclosed world. What we will find, through an engagement with a range of anarchist and anarchistic theory, is that Mbembe's Open World has deep resonances with the world sought by anarchists; it is an anarchic world rooted in a prefigurative practice that un-forecloses the future.